EFFECTS OF DIETARY FUCOIDAN SUPPLEMENTATION ON GROWTH, IMMUNITY, AND DISEASE RESISTANCE IN RED SWAMP CRAYFISH (Procambarus clarkii) - Yusi Lan; Yu Liu; Xue Li; Yingming Mao; Xiang Li; Shengjun Wu (Journal of Animal and Plant Sciences, 2025)
Fucoidan is a polysaccharide that has antioxidant activity, antibacterial activity, antiviral activity, immunomodulatory activity, and hypolipidemic activity. This study aimed to evaluate the impact of fucoidan supplementation on the growth performance, immune response, and disease resistance of Red Swamp crayfish (Procambarus clarkii). The effects of different levels of fucoidan supplementation [0 (F0), 1 g/kg (F1), 3 g/kg (F3), and 5 g/kg (F5)] in the diets of Red Swamp crayfish were evaluated. Fucoidan supplementation significantly improved growth performance, immune activity, and disease resistance in the crayfish, with the highest benefits observed at 3% and 5% fucoidan inclusion. A high dosage (F5) did not improve the growth properties compared with a medium dosage (F3) may because of the hypolipidemic activity. Dietary 3 g/kg of fucoidan increased survival rate, body weight gain rate, specific growth rate and food efficiency by 21.51%, 34.51%, 11.43% and 39.39% compared with those of the control group. The optimal dose of dietary fucoidan supplementation required for the maximum growth of crayfish was 3 g/kg. These findings suggest that fucoidan supplementation can be an effective strategy to enhance both the growth and health of Red Swamp crayfish.
Keywords: growth; body trophic component; innate immunity